2018
DOI: 10.1038/s41598-018-35436-x
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of precipitation and temperature to the large scale geographic distribution of fleshy-fruited plant species: Growth form matters

Abstract: Fruit type, an important reproductive trait, is closely related to reproduction strategy, community dynamics and biotic interactions. However, limited research has explored the geographic distribution of fruit type and the underlying abiotic factors influencing this on a large scale. Here we aim to study large-scale distribution patterns of fleshy-fruited plant species and the most important environmental drivers for different growth forms in utilizing the fruit type and distribution data for over 27000 plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 58 publications
2
38
3
1
Order By: Relevance
“…Because there are few inventory‐based species checklists of vascular plants at the spatial scale of 10 000 km 2 in China, we are not able to assess the degree of completeness of the species lists used in this study for 100 × 100 km grid cells. Considering that the species lists of 100 × 100 km grid cells reported by Lu et al (2018) and by others for Chinese plants have been commonly used in macroecological studies (Feng et al 2016, Lu et al 2018, Xu et al 2018, Zhao et al 2018, Ye et al 2019), the use of occurrence data compiled for Chinese plants in 100 × 100 km grid cells in the present study is consistent with the current literature. Furthermore, because the plant data used in this study is an updated version of the data reported by Lu et al (2018), with 10.5 millions of specimen records from NSII and GBIF (Qian et al 2018) and over 200 local and regional floras (Qian et al 2017, 2018) having been used to update Lu et al's data, we believe the species lists used in this study are more complete than those used in most, if not all, of previous macroecological studies on Chinese plants at the spatial scale of 10 000 km 2 .…”
Section: Methodssupporting
confidence: 90%
“…Because there are few inventory‐based species checklists of vascular plants at the spatial scale of 10 000 km 2 in China, we are not able to assess the degree of completeness of the species lists used in this study for 100 × 100 km grid cells. Considering that the species lists of 100 × 100 km grid cells reported by Lu et al (2018) and by others for Chinese plants have been commonly used in macroecological studies (Feng et al 2016, Lu et al 2018, Xu et al 2018, Zhao et al 2018, Ye et al 2019), the use of occurrence data compiled for Chinese plants in 100 × 100 km grid cells in the present study is consistent with the current literature. Furthermore, because the plant data used in this study is an updated version of the data reported by Lu et al (2018), with 10.5 millions of specimen records from NSII and GBIF (Qian et al 2018) and over 200 local and regional floras (Qian et al 2017, 2018) having been used to update Lu et al's data, we believe the species lists used in this study are more complete than those used in most, if not all, of previous macroecological studies on Chinese plants at the spatial scale of 10 000 km 2 .…”
Section: Methodssupporting
confidence: 90%
“…This might be due to the fact that neither temperature nor precipitation alone could reflect the actual amount of energy and water that plants use for growth (Moles et al, 2014). These findings are in contrast with previous studies on the determinants of fruit type compositions (Chen et al, 2017;Zhao et al, 2018). For example, a recent study on the geographical pattern in the prevalence of fleshy-fruited angiosperm species in Australia (Chen et al, 2017) indicated that precipitation dominated the geographical variations in the proportion of fleshy-fruited species.…”
Section: Effects Of Contemporary Environment On Fruit Type Compositionmentioning
confidence: 76%
“…The development, formation and distribution of plants are closely integrated with climate factors, especially temperature and precipitation [31]. First, we found that the variables contributing to the models of the four species were isothermality (Bio3) and mean temperature of the warmest quarter (Bio10).…”
Section: Discussionmentioning
confidence: 91%
“…Changes in the areas and centroids of the highly suitable habitats for Gentiana macrophylla Pall and unchanged areas under future climate scenariosDiscussionThe development, formation and distribution of plants are closely integrated with climate factors, especially temperature and precipitation[31]. First, we found that the variables contributing to the models of the four species were isothermality (Bio3) and mean temperature of the warmest quarter (Bio10).…”
mentioning
confidence: 88%